2005
DOI: 10.1371/journal.pmed.0030013
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling Predicts Survival in Conventional Renal Cell Carcinoma

Abstract: BackgroundConventional renal cell carcinoma (cRCC) accounts for most of the deaths due to kidney cancer. Tumor stage, grade, and patient performance status are used currently to predict survival after surgery. Our goal was to identify gene expression features, using comprehensive gene expression profiling, that correlate with survival.Methods and FindingsGene expression profiles were determined in 177 primary cRCCs using DNA microarrays. Unsupervised hierarchical clustering analysis segregated cRCC into five g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
193
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(210 citation statements)
references
References 29 publications
13
193
0
4
Order By: Relevance
“…The results suggested that 2 molecularly distinct forms of clearcell RCC exist and that the integration of expression-profile data with clinical parameters could enhance the diagnosis and prognosis of clearcell RCC. More recently, a study of 177 clearcell RCC tumours 38 elicited a set of genes whose expression of mRNA correlated significantly with length of survival after surgery, even after controlling for conventional clinical parameters. Notably, overlapping genes were found in both studies, 37,38 further confirming the underlying molecular difference between nonaggressive and aggressive tumours and their clinical behaviour.…”
Section: Prognosis By Gene-expression Profilingmentioning
confidence: 99%
See 1 more Smart Citation
“…The results suggested that 2 molecularly distinct forms of clearcell RCC exist and that the integration of expression-profile data with clinical parameters could enhance the diagnosis and prognosis of clearcell RCC. More recently, a study of 177 clearcell RCC tumours 38 elicited a set of genes whose expression of mRNA correlated significantly with length of survival after surgery, even after controlling for conventional clinical parameters. Notably, overlapping genes were found in both studies, 37,38 further confirming the underlying molecular difference between nonaggressive and aggressive tumours and their clinical behaviour.…”
Section: Prognosis By Gene-expression Profilingmentioning
confidence: 99%
“…More recently, a study of 177 clearcell RCC tumours 38 elicited a set of genes whose expression of mRNA correlated significantly with length of survival after surgery, even after controlling for conventional clinical parameters. Notably, overlapping genes were found in both studies, 37,38 further confirming the underlying molecular difference between nonaggressive and aggressive tumours and their clinical behaviour. This finding has significant clinical implications for intervention strategies.…”
Section: Prognosis By Gene-expression Profilingmentioning
confidence: 99%
“…Prolyl hydroxylase-3 (PHD3/ENGL3) is a member of the PHD family, which is involved in the degradation of HIF proteins in cooperation with VHL protein under normoxic conditions. PHD3 was found frequently over-expressed in RCC tissues, with high specificity to cancer samples (Zhao et al, 2006) and its usefulness as a novel tumor antigen for RCC immunotherapy has been recently demonstrated in clinical serum samples from RCC patients (Sato, 2008;Tanaka, 2011). Insulin-like growth factor binding protein 3 (IGFBP3) is one of the most over-expressed genes in ccRCC (Takahashi, 2005;Yao, 2005) and its increased protein expression has been demonstrated in 74% of ccRCCs by IHC and associated with higher Fuhrman nuclear grade (Chuang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…survival time) to certain explanatory variables. New methodologies were developed for calculating the survival probabilities using gene expression profiles when genome-wide expression data becomes increasingly available in the past two decades [38][39][40][41][42].…”
Section: Identifying Survival-related Genes Of Patients With Breast Cmentioning
confidence: 99%